2023
DOI: 10.1590/1519-6984.248978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gastrointestinal parasite in small ruminants of District Dir Upper Khyber Pakhtunkhwa Province of Pakistan

Abstract: The present research was planned to assess the occurrence of intestinal parasites in small ruminants of Upper Dir of Khyber Pakhtunkhwa Province of Pakistan. For this purpose, the faecal material was collected randomly with gloved fingers directly from the rectum region of sheep and goats and the faecal materials were then put in hygienic plastic bottles with 10% formalin. The overall 315 (n=184 sheep and n= 131 goats) faecal samples were collected out of 315 samples, 281 were found positive for different para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
8
1
1
Order By: Relevance
“…It is also observed that none of the upper 95%CI for bucks and Does was less than 1 meaning none of the factors was considered a protective factor. Hassan et al, 2019;Ruhoollah et al, 2021;Yusof et al, 2016).…”
Section: Results and Discusionmentioning
confidence: 99%
“…It is also observed that none of the upper 95%CI for bucks and Does was less than 1 meaning none of the factors was considered a protective factor. Hassan et al, 2019;Ruhoollah et al, 2021;Yusof et al, 2016).…”
Section: Results and Discusionmentioning
confidence: 99%
“…In the present study, distinguishing Trichuris females corresponding to each species of male was difficult because of coinfection with several species. Therefore, females were not identified in this study, and the identification of Trichuris species was based on the key characteristics of the reproductive organs of adult males as is common practice (6,11,15,20). Studies have revealed that the features such as the body length, the whip length to body length proportion, the length of the spicule and its sheath, and the morphometric characteristics of the spines of the spicule sheath are of high discriminatory value in differentiating Trichuris species (6,11).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological identification of Trichuris spp. was based on the size of the adult male worm, the ratio of whip to body, the length of the copulatory spine, and the shape and size of the spiny sheath (6,11,20,22,26,27). All individuals of Trichuris spp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species Т. ovis is registered in Albania, Azores, Belarus, Great Britain, Bulgaria, Russia, Cyprus, India, Estonia, USA, China, Turkey, France, United Kingdom, Germany, Hungary, Iceland, Italy, Lithuania, Poland, Spain, Canada, Philippines, Australia, Africa, Sweden, the Netherlands, Pakistan, Nigeria, South America, and Ukraine (Morales et al, 2001;Kuchai et al, 2011;de Jong et al, 2014;Jegede et al, 2015;de Jong, 2016;Ruhoollah, Khan et al, 2021). The GBIF Information System platform has 175 georeferenced distribution records T. ovis in the world (Fig.…”
Section: Introductionmentioning
confidence: 99%